Hyperpolarized noble gas magnetic resonance imaging of the ex vivo rodent lung - Lilburn, D.M.L. (2015)
The work described within this thesis was conducted at the University of Nottingham between April 2011 and March 2014. Due to the inter-disciplinary nature of this work it was undertaken by the author in conjunction with the other scientists in the Translational Imaging group at the Sir Peter Mansfield Magnetic Resonance Centre, University of Nottingham and collaborators in both the Pulmonary Biology group, University of Nottingham and the Respiratory Pharmacology group, Imperial College London. Pulmonary hyperpolarized (hp) noble gas magnetic resonance imaging (MRI) has seen increasing development and utility over the past two decades. However the application of this relatively new pulmonary imaging modality to small animal models is technically challenging. Ex vivo lung models have allowed for the investigation of functional respiratory measurements in small animals but have yet to be utilized with hp noble gas MRI. The ex vivo lung model presented within this work allowed for the study of pulmonary physiology using hp 129Xe and hp 83Kr MR imaging in intact lungs from both healthy rodents and rat models of respiratory disease. Novel hp 129Xe imaging protocols were developed to provide measurements of functional respiratory parameters and to gather information of regional gas distribution in healthy excised rodent lungs. Furthermore the developed 129Xe methodology was used to study regional responses in an ex vivo model of human asthma after intravenous deliveries of increasing quantities of the bronchoconstricting agent methacholine. The ex vivo model provided the platform to develop the novel lung imaging technique of hp 83Kr surface quadrupolar relaxation (SQUARE) MRI with this new methodology used to study an excised rat model of emphysema potentially providing the first application for this quadrupolar noble gas isotope in the field of respiratory medicine.